2021
DOI: 10.3389/fonc.2021.687362
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid: A Promising Therapeutic Agent in Glioma Treatment

Abstract: Glioma, characterized by infiltrative growth and treatment resistance, is regarded as the most prevalent intracranial malignant tumor. Due to its poor prognosis, accumulating investigation has been performed for improvement of overall survival (OS) and progression-free survival (PFS) in glioma patients. Valproic acid (VPA), one of the most common histone deacetylase inhibitors (HDACIs), has been detected to directly or synergistically exert inhibitory effects on glioma in vitro and in vivo. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 97 publications
(130 reference statements)
0
21
0
Order By: Relevance
“…We observed that a low degree of enrichment, i.e., low activity, for “IDL particle”, “negative regulation of sterol transport” and “Valproic acid” corresponded to poor survival in samples with higher glioma grade. Interestingly, “Valproic acid” ( Figure 5 C,G,K) has been recently proposed as a promising therapeutic target for gliomas [ 71 ]. We also noticed that microtubule-related annotations did not influence the overall survival ( Figure 5 D,H).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that a low degree of enrichment, i.e., low activity, for “IDL particle”, “negative regulation of sterol transport” and “Valproic acid” corresponded to poor survival in samples with higher glioma grade. Interestingly, “Valproic acid” ( Figure 5 C,G,K) has been recently proposed as a promising therapeutic target for gliomas [ 71 ]. We also noticed that microtubule-related annotations did not influence the overall survival ( Figure 5 D,H).…”
Section: Resultsmentioning
confidence: 99%
“…The above studies suggest that though VPA possesses substantial advantages in the treatment of cancer both in vitro and in vivo, the controversial treatment effects of VPA on certain types of cancer can still be observed. Further studies to access the efficacy, safety, and durability of VPA treatment Due to its inhibitory effect on HDAC, which is shown to be involved in cancer progression, metastasis, and recurrent, numerous reports have demonstrated the potential anti-cancer properties of VPA [100,[105][106][107][108]. Indeed, there have been reports showing the application of VPA in clinical trials.…”
Section: The Effect Of Valproic Acid In Anti-cancer Therapymentioning
confidence: 99%
“…Due to its inhibitory effect on HDAC, which is shown to be involved in cancer progression, metastasis, and recurrent, numerous reports have demonstrated the potential anti-cancer properties of VPA [ 100 , 105 , 106 , 107 , 108 ]. Indeed, there have been reports showing the application of VPA in clinical trials.…”
Section: Repurposing Anesthetic/sedative Drugs Into Anticancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approved drug that emerged as an interesting therapeutic in GBM is valproic acid (VPA). It has been demonstrated that VPA inhibited glioma cell proliferation, migration, and invasion [ 362 ]. Experiments on human GBM cell lines have shown that VPA had a strong antiproliferative effect and also led to a reduction in CD44 expression (a cancer stem cell marker) [ 363 ].…”
Section: Targeting Hippo Signaling Pathway In Gbmmentioning
confidence: 99%